An analysis of the relationship between psychosocial safety climate and the work-school-interface for non-traditional students in South Africa - April, Kelly (Organisational Psychology, 2022)
The growth of a country's economy is highly dependent on the levels of skills available in that country. South Africa has a stark shortage of skilled individuals due to an inadequate and failing education system (Horwitz, 2013). As a response to this problem the South African government actively incentivises organisations to develop the skillset of their employees in order to build a strong economy, improve job creation and promote social development (Department of Higher Education and Training, 2019). It is therefore important that all stakeholders involved yield a return on this investment. It is also a global phenomenon that an increasing number of fulltime employees are also engaging in formal further studies due to the rapid changes in the labour market. For example, advancements in technology have had a major impact on traditional business models and the roles, and skills needed. These employees are referred to as non-traditional students and are the subject of this study. Research shows that trying to manage both work and school simultaneously can cause psychological strain for non-traditional students (Adebayo et al., 2008). The psychosocial safety climate (PSC) is an emerging construct which refers to the shared perceptions regarding policies, practices and procedures designed to protect the psychological health of employees (Dollard et al., 2012). This study builds on existing research in the work - school interface by investigating its application within the South African context. Participants in this research (n=127), comprised of non-traditional students (n=40) and employees who are not engaged in further studies (n=87). Correlation analysis demonstrated that PSC had a positive relationship with work school facilitation (WSF) and a negative relationship with work school conflict (WSC). It was further confirmed that job control (JC) mediated the relationship between PSC and WSF and that PSC mediated the relationship between JC and WSF. These findings show that PSC is an antecedent to the work school interface in that it promotes the positive outcomes of studying while working (work school facilitation). It further demonstrates that PSC also reduces the negative outcomes (work school conflict). This study confirmed that the working environment plays a crucial role in the work school interface and introduces PSC as a construct South African organisations should be concerned with and make a priority, based on the resources it provides employees, more especially their non-traditional students. This study's findings will add to the existing body of research and provide practical insights for enhancing the PSC application within South African organisations who have non-traditional students.